"The magic triangle between bed, office, couch": a qualitative exploration of job demands, resources, coping, and the role of leadership in remote work during the COVID-19 pandemic - Elisabeth Rohwer; Volker Harth; Stefanie Mache (BMC, 2024)
Abstract Background The COVID-19 pandemic has necessitated many employees to work from home with immediate effect for several months, regardless of their workplace preference or situation at home. Against this backdrop, this study explores perceived job demands and resources as well as the role of leadership and coping strategies of employees and managers with little or no prior experience with working from home in the altered work environment. Methods Based on the job demands-resources model, we developed an interview guide and conducted thirty-four semi-structured interviews. The interviews were transcribed and analyzed deductively-inductively using qualitative content analysis. Results Experienced job demands include, e.g., challenging, insufficient digital communication, and lack of social exchange, while greater flexibility and work-life balance were identified as valuable resources. Regarding the role of leadership, signaling trust, keeping regular contact, and supporting employees are important. To cope with the unforeseen yet persistent work situation, participants applied creative strategies by setting up offices at home with what they had at disposal. Differences were observed between employee and managerial perceptions as well as over time during the pandemic. Conclusions The results expand our knowledge about healthy remote work by adding specific demands, resources, and coping strategies employees and managers experienced during the extreme situation of the COVID-19 pandemic to the picture as well as specifying the role of leadership. Moreover, our findings provide a foundation for guidelines for healthy remote work design and collaboration in times of abrupt change and crises.